AN AUTOPSY BASED 03 YEAR RETROSPECTIVE STUDY ABOUT DEMOGRAPHIC PROFILE, PATTERN OF INJURIES AND CAUSE OF DEATH IN THE ELECTROCUTION CASES AT CENTRAL INDIA REGION (Journal of Forensic Medicine & Toxicology, 2021)
Electricity has become our life line in today’s world, its hard to imagine life without it. But along with its great advantages and conveniences, it also brings imminent danger to our life. Morbidity and mortality associated with electrical burns are usually preventable with adoption or application of basic safety measures. The present study was based on retrospective analysis of electrocution burn cases performed during the period from 1st January 2018 to 31st December 2020 in the Department of Forensic Medicine and Toxicology, M.G.M. Medical College, Indore (M.P). This study comprised 95 cases brought with the history of electrocution, consisting of 84 males and 11 females. Majority of the victims belonged to the age group of 21-30 years. In, 55.79 % victims only entry marks were seen and 17.89 % showed both entry and exit mark. Joule burns were seen in 68.42% of victim where as flame burns in 21.05%. Upper limbs were commonly involved in 57.89% cases and become
Keywords: Electrocution; Entry and Exit mark; Joule burn; Flame burn